Importancia en la aplicación de las NIIF para pymes teniendo en cuenta la sección 13 inventarios. (2020)
This academic exercise focuses on making visible the importance of applying the IFRS accounting framework, taking into account Section 13 Inventories. In this same order and direction, the article takes as a starting point, the generalities of the subject under study, that is, the definition of inventory in an accounting context. The second part corresponds to the review of the background of Colombian SMEs in relation to the inventory issue, including a general outline of the inventory issue in our country.The third part presents the explanation of inventory measurement, including its two types, initial measurement and subsequent measurement in the IFRS accounting framework. The fourth part refers to the comparative relationship between IFRS SMEs Differences and GAAP. Later in the article an analysis of the impact of this section 13 inventories in the SME union is carried out. As a conclusion, a final reflection on the subject under study is socialized. The document is approached from the methodological framework under the guidelines of a descriptive research, because it is going to talk about a single topic, so it was necessary to report and describe the most relevant characteristics of this section 13 Inventories of the IFRS accounting framework. In accordance with the determined approach, documentary referencing was used as a source for gathering information from journals, consultation texts, both physical and virtual